Animating for “The Hole in the Wall” - Ashia Abdullah Kobayashi (Nanyang Technological University, 2022)
“The Hole in the Wall” is an upcoming 2D animated character-driven film about a Singaporean man named Finnick. Passive and listless towards life despite his flourishing circumstances, he soon discovers happiness from the music emitted by a mysterious hole in the wall of his new HDB apartment. Finnick would ultimately sacrifice the life he had to drown himself in the hole’s blissful abyss. Original avant-garde music turns Finnick’s brutalist Singaporean home into a surreal landscape. His circumstance in the story represents the worst of Generation Z's anxieties towards the expectations of adulthood and what comes after.